Innovative and sustainable green concrete–A potential review on utilization of agricultural waste. (August 2019) - Mohamad, Noridah; Tahir Lakhiar, Muhammad; Aziz Abdul Samad, Abdul; Othuman Mydin, Md Azree; Ahmed Jhatial, Ashfaque; Anis Sofia, S.; Inn Goh, Wan; Ali, Noorwirdawati
Abstract: Concrete is the most versatile product used as building material in world's construction industry, and it generates carbon to the atmosphere. In manufacturing of cement, 8% to 10% of global carbon dioxide (CO2 ) gas is generated. The maximum utilization of cement contributes to global warming and climate change. Therefore, many scholars have conducted a research to develop green and sustainable concrete incorporating different waste materials. By utilizing waste materials as cement replacement, the CO2 gas emissions will decrease. This paper reviews the potential and innovative utilization of agricultural waste as partially cement replacing material to make green concrete. Agricultural waste possesses the pozzolanic materials, when finely grinded, generate pozzolanic reaction, in which silica responds with calcium oxide to create calcium silicates which is responsible for higher strength attained in the concrete. It is concluded from previous studies the agricultural waste which consist the high silica contain generated the pozzolanic reaction in concrete mix which contributes the enhancement in strength. The RHA, SCBA POFA are the pozzolanic material, 10%-20% utilization of these waste is optimum and enhance the 20%-30% strength of concrete. The Banana Skin Powder (BSP) also possesses the high silica contain which will generate the pozzolanic reaction in concrete mix and will improve the strength of concrete such as the other agricultural waste improves.